The Samaritans in Flavius Josephus. By Reinhard Pummer - Coggins, Richard (The journal of theological studies, 2011)
The origins and early history of the Samaritans have long been topics of deep and at times virulent controversy, and here, as in his many previous studies, Reinhard Pummer has provided one of the calmer voices, looking dispassionately at the evidence rather than pursuing some predetermined agenda. One major problem for interpreters has been the variety of sources providing references to the early Samaritans—the Hebrew Bible, the Qumran scrolls, later Jewish texts, early Christian writings, the Samaritans’ own Chronicles, and in particular the work of Josephus, which has been very variously understood. In addition, recent archaeological work in the area of Mount Gerizim has challenged some views of early Samaritanism.